Dffierent Effects of Human Neutrophil Elastase on Platelet Glycoproteins IIb and IIIa of Resting and Stimulated Platelets - Bykowska, K; Pawlowska, Z; Cierniewski, C; Lopaciuk, S; Kopeć, M (Thrombosis and Haemostasis, 1990)
The effect of human neutrophil elastase (HNE) on the structure and receptor activity of platelet glycoprotein IIb/IIIa complex was studied. Resting platelets, which bound only traces of 125I-fibrinogen in the absence of ADR were found to be barely susceptible to HNE. As shown by immunoblotting experiments, treatment of such platelets with HNE (14 μg/ml) did not provoke a detectable cleavage of GPIIb but resulted in a partial digestion of GPIIIa and appearance of 110 kDa fragment. Such proteolytic modification of the GPIIb/IIIa complex was accompanied by a slight increase in the binding of fibrinogen to blood platelets in the absence of ADP. Treatment of partially activated platelets (spontaneous activation during washing procedure) with HNE caused a progressive loss of GPIIb and degradation of GPIIIa to 110 kDa and 60 kDa fragments. These spontaneously stimulated platelets had initially a high number of fibrinogen binding sites exposed, corresponding to approximately 50% of receptor capacity observed in platelets activated by the optimal concentration of ADP. Digestion of GPIIb/IIIa by HNE of such platelets markedly increased the exposure of fibrinogen receptors. Thus, the stimulation of platelets increases significantly the susceptibility of the GPIIb/IIIa complex to proteolysis by HNE. However, such modification of the GPIIb/IIIa does not destroy its function as a receptor for fibrinogen either on the resting or activated platelets.